Impact of Poverty on Adolescent Drug Use: Moderation Effects of Family Support and Self-Esteem. Issue 4 (1st October 2020) - Lee, Kyunghee; Clancy, Bridget
ABSTRACT: Using data from the National Longitudinal Survey of Youth, this study examined 2 questions: (a) Does poverty affect adolescents' drug use, controlling for individual, family, and contextual characteristics and does this differ depending on race or ethnicity? (b) Are adolescent self-esteem and family support associated with their drug use? Findings suggest that living in poverty had adverse effects on adolescent drug use. Compared to Black and Hispanic youth, these effects were more pronounced among White adolescents living in poverty. Adolescents with higher self-esteem were less likely to use drugs. Drug use differed depending on gender, number of siblings, maternal marital status, and maternal years of education. This study suggests that substance use should be addressed in ecological contexts, looking at both macro antipoverty programs and micro psychosocial and family support programs. Current policies should expand on and bring new prevention and intervention efforts to reduce adolescent drug use by considering these macro and micro factors.